PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DANA BAGI HASIL TERHADAP BELANJA MODAL (Studi pada Provinsi/Wilayah Kalimantan dan Sulawesi) - Dina Mei Eka Aditya, 14.05.52.0238; Maryono, Maryono (Students Journal of Accounting and Banking, 2018)
This study aims to examine the effect of the Original Income of General Allocation Funds, Special Allocation Funds, and Profit Sharing Funds for Capital Expenditure in Kalimantan and Sulawesi Provinces/Regions 2012-2015. The type of data used is secondary data from the financial statements years each province. The sampel obtained is 42 data. Data collection techniques using documentation techniques. Research data were then tested using multiple regression analysis. The result of the research shows that the local revenue is positively significant to the Capital Expenditure. General Allocation Fund has significant negative effect to Capital Expenditure. The Special Allocation Fund has a significant positive effect on Capital Expenditure. Revenue Sharing Funds has a significant positive effect on Capital Expenditure.Keywords: The Original Income Areas, General Allocation Funds, Adana The Allocation of Special Funds For The Result, Capital Expenditures